The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1002/chem.200902465
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Switching of a Micelle‐to‐Vesicle Transition by Compressed CO2

Abstract: The study of the micelle-to-vesicle transition (MVT) is of great importance from both theoretical and practical points of view. Herein, we studied the effect of compressed CO(2) on the aggregation behavior of dodecyltrimethylammonium bromide (DTAB)/sodium dodecyl sulfate (SDS) mixed surfactants in aqueous solution by means of direct observation, turbidity and conductivity measurements, steady-state fluorescence, time-resolved fluorescence quenching (TRFQ), fluorescence quantum yield, and template methods. Inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
21
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 88 publications
1
21
0
Order By: Relevance
“…Application of this principle has been studied in controlling the properties of different surfactant assemblies, such as reverse micelles, 18-20 micelles, 21 vesicles, 22 and switching phase transition between them. 23,24 In a previous paper, we found that CO 2 is also efficient in tuning the properties of an emulsion system, which is stabilized by a anionic surfactant of bis-2-ethylhexylsulfosuccinate (AOT). 25 In comparison with the conventional methods to tune the properties of surfactant systems (adding solid or liquid additives), the use of CO 2 has many advantages.…”
Section: Introductionmentioning
confidence: 99%
“…Application of this principle has been studied in controlling the properties of different surfactant assemblies, such as reverse micelles, 18-20 micelles, 21 vesicles, 22 and switching phase transition between them. 23,24 In a previous paper, we found that CO 2 is also efficient in tuning the properties of an emulsion system, which is stabilized by a anionic surfactant of bis-2-ethylhexylsulfosuccinate (AOT). 25 In comparison with the conventional methods to tune the properties of surfactant systems (adding solid or liquid additives), the use of CO 2 has many advantages.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, with the progress in sustainable chemistry, supercritical or compressed CO 2 has been widely used in many aspects. [11] Compressed CO 2 can trigger the formation of nanoemulsions reversibly, [12] and switch the micelle-tovesicle transition (MVT) [13] and the liquid-crystal-to-micelle transition. [14] Furthermore, by regulating the pressure, compressed CO 2 favors the separation of the products.…”
mentioning
confidence: 99%
“…In recent years, with the progress in sustainable chemistry, supercritical or compressed CO 2 has been widely used in many aspects 11. Compressed CO 2 can trigger the formation of nanoemulsions reversibly,12 and switch the micelle‐to‐vesicle transition (MVT)13 and the liquid‐crystal‐to‐micelle transition 14. Furthermore, by regulating the pressure, compressed CO 2 favors the separation of the products 15.…”
Section: Methodsmentioning
confidence: 99%